MDCM, Inc. (B) : strategic IT portfolio management - Jeffery, Mark; Yung, Derek; Norton, Joseph F. (London : Kellogg School of Management, 2006)
The case examines the steps involved in developing a portfolio of IT projects aligned with a company's strategic objectives. Specifically, the case describes a situation where a firm has launched a transformation strategy but has yet to develop a complementary IT strategy. Students must select the optimal portfolio of projects aligned with the strategic objectives and define the global project execution strategy.
Originally published in Jeffery, M., Yung, D., & Norton, J. F. (2006). MDCM, Inc. (B): Strategic IT portfolio management. 5-404-770(B). Evanston, IL: Kellogg School of Management at Northwestern University.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; MDCM, Inc; Industrial management -- Data processing; Horizon 2000.